The ICT teacher's handbook : teaching, learning and managing ICT in the secondary school - Crawford, Roger, ....- (London : Routledge, 2013)
The ICT Teacher's Handbook is an indispensable guide for all teachers responsible for the teaching and management of ICT in the secondary school, both as a comprehensive introduction for students learning to teach ICT and as a source of ongoing support for busy practising teachers. Illustrated throughout with case studies, key further reading and guidance on where to find and how to choose the best software and resources, the book also features a guide to specifications, software for whole school support and a useful glossary of key terms. Key topics covered include: Organising and delivering the ICT National Curriculum at key stages 3 and 4 and post 16 Teaching and learning with VLEs, IWBs, social networking and mobile technologies Assessment, record keeping and reporting Popular hardware, software and networks External assessment, target setting and tracking Managing technical support and technicians Preparing for promotion and managing an ICT department Strategies for whole school management of ICT Written for trainee and experienced ICT teachers and managers in both English and international schools, The ICT Teacher's Handbook is an authoritative guide designed to support effective teaching and learning, and efficient use of technology in all schools.
Keywords: ICT ; onderwijs ; secundair onderwijs